An equivalent diffusion coefficient model of the oxidation of ceramic matrix composites. Issue 15 (1st August 2021) - Yu, Guoqiang; Shi, Xiaoting; Wang, Yuanhong; Du, Jinkang; Ni, Zheng; Gao, Xiguang; Wang, Fang; Song, Yingdong
Abstract: A multiscale analysis method was developed to simulate the reaction-diffusion process of SiC/SiC composite structures in a coupled thermo-chemo-mechanical environment. For the diffusion process, the airflow channel was characterized by an equivalent diffusion coefficient model, which was established in this study. The corresponding calculation was developed using a numerical analysis method to obtain the gas concentration distribution in the structure. For the reaction process, an oxidation kinetics model was adopted to calculate morphological evolution of the airflow channel. The equivalent diffusion coefficient was then updated, and the reaction–diffusion coupling calculation was performed through an iterative scheme. To validate the model, an oxidation tensile test was conducted at 1200 °C. Finally, an adjustment sheet model was calculated as an example to analyze its reaction-diffusion process, proving that this method can be applied to SiC/SiC components under complex aerodynamic and temperature loads.